Meningkatkan Motivasi Menghafal Al Quran Melalui Metode Halaqoh di MTs Buluspesantren - Muhibbatun Soodiqoh; Siti Fatimah; Faisal Faisal (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This article was written using the Classroom Action Research (CAR) method. The type of research used is qualitative research. The research subjects were class VIII A students of MTs Buluspesantren for the 2023/2024 academic year. The research was conducted to find out how far the motivation of MTs Bulus Pesantren students is in memorizing the Al-Qur'an through the halaqoh method. The data that has been collected through the methods of observation, questionnaires, and assignments are then analyzed through cycle I and cycle II in the application of learning. The results showed that in the first cycle there was an increase of 30% from before the halaqoh method was implemented, so that in the first cycle it increased to 50% of students who got a complete score in memorizing the Qur'an. Whereas in cycle II there was a very good increase of 85% of students who got a complete score in memorizing the Al-Qur'an. In addition, after the implementation of the halaqoh method in the process of memorizing the Qur'an, MTs Buluspesantren students were able to understand what was conveyed by the teacher. So that the targeted deposit is achieved as expected. And also MTs Buluspesantren students compete with each other to deposit verses of the Qur'an with enthusiasm.